Integrating STEM Education with Bilingual Instruction: An Innovative Teaching Design for Introduction to Civil Engineering in Sino-foreign Cooperative Education - Zhang, Fuxia; Wang, Jianxiong (Journal of Dhamma for Life, 2025)
This research presents an innovative teaching design that integrates STEM education principles with bilingual instruction for the Introduction to Civil Engineering course in Sino-foreign cooperative education programs. The study addresses critical challenges in engineering education, including the disconnection between language acquisition and professional knowledge construction, and the gap between traditional teaching methods and modern engineering requirements. Based on the theoretical framework combining STEM education, bilingual teaching theory, and constructivism, this research proposes a comprehensive teaching design featuring modular content organization, project-based learning activities, and a multi-dimensional assessment system. The design introduces several innovative elements, including the "Tofu Engineering" project, which transforms abstract foundation engineering concepts into tangible experiences. Drawing from eight years of implementation experience with 646 students at Yunnan Agricultural University's Sino-foreign cooperative program, the study provides detailed implementation pathways and recommendations for faculty development. The research contributes to the advancement of engineering education pedagogy by offering a systematic approach to simultaneously developing students' professional competence and language proficiency, while accommodating diverse learning needs in international engineering education contexts. Funding: This research was supported by the Third Batch of Online and Offline Hybrid First-class Undergraduate Course Construction Project of Yunnan Agricultural University in 2023 (2023YLKC067).